Beban Kerja Perawat dengan Reseliensi di Rumah Sakit Islam Purwokerto - Etlidawati Etlidawati; Retno Sulistiyowati; Alfi Noviyana (Jurnal Keperawatan Silampari, 2022)
This study analyzes the relationship between nurse workload and resilience at the Islamic Hospital in Purwokerto. This research method is quantitative research using a correlation design with a cross-sectional approach. The results showed that the light workload was 56% and the heavy workload was 44%. Low resolution 73%, high resolution 27%. The test results obtained a p-value of 0.003 with an OR of 0.435. In conclusion, there is a strong relationship between nurse workload and resilience in the inpatient room of the Purwokerto Islamic Hospital Keywords: Workload, Nurses, Resilience